Modification of the Release Profiles of Theophylline Matrix Tablets by inclusion of Water Leachable or Water Swellable Excipients - Avbunudiogba, J. A (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Matrix system is an attractive oral controlled release dosage form due to convenience in process development and low production. This study was undertaken to investigate the effects of leaching and swelling agents on sustained release theophylline tablets. Twelve batches of theophylline matrix tablets were prepared with ten batches containing varied amount of the swellant or channeling agents. The matrix tablets were prepared by either melt granulation or simple coacervation technique. Release studies were carried out for 12 h in 0.1 N HCl. Data obtained were fitted into zero order, first order, Higuchi and Korsmeyer equations. The initial release after 60 min and maximum release from only carnauba wax and Eudragit based tablets were 13%, 50% and 12.5%, 46% respectively. With the inclusion of 10% sucrose, these values were increased to 22%, 80% and 22%, 86% respectively. Both the rate and extent of release were significantly increased with the inclusion of either channeling agents or swellant. Kinetic study revealed that the mechanism of release was mainly by diffusion and partly by erosion. Thus, the inclusion of excipients in the right proportion can produce matrix tablets with desired release profiles.